An integrated analysis of match-related fatigue in professional rugby league - Kempton, T.; Sirotic, A. C.; Coutts, A. J. (Journal of Sports Sciences, 2015)
This study examined the changes in external outputs, including metabolic power variables, and internal response whilst considering contextual factors on physical performance variables during rugby league match play. Physical performance (total distance, high-speed running and high-power distances, average metabolic power), heart-rate (percentage heart-rate peak and training impulse), collisions (attacking and defensive) and contextual (time in attack, time in defence, time out of play) data were collected from 18 rugby league players during 38 games throughout two National Rugby League seasons. Physical variables were highest in the first 10-min period of each half (P < 0.001). Heart-rate indices peaked in the second 10-min period and were lower during second half periods (P < 0.001). Few differences existed in collisions and contextual factors across 10-min periods. Physical variables were highest during the first 5-min period compared to the final (P < 0.001). There was no difference in heart-rate response, attacking collisions or contextual factors between these periods. Following the peak 5-min period in the match, there were reductions in physical, heart-rate, defensive collisions and contextual factors (P < 0.001). The data show temporal changes in physical performance, heart-rate response and collisions during rugby league match play, although these are affected by contextual factors.